The Impact Of Firm Size, Managerial Ownership And Collateralizable Asset On Dividend Policy In Indexs Lq45 Companies - Witanto, Herlina; Lesmana, Desy (Jurnal Informasi Akuntansi (JIA), 2023)
The study aims to analyze the influence of firm size, managerial ownership and collateralizable assets of dividend policy by focusing on companies listed in LQ45 index with research period in 2016-2020. The data used in this research are secondary data. The population in this study are LQ45 index companies. The sampling selection method used was purposive sampling and obtained 13 companies with a total of 65 samples. The analytical tool used in this study was the linear regression analysis. The results of this research showed that firm size negatively affects dividend policy while managerial ownership and collateralizable assets positively affect dividend policy